THE DISCIPLINE DANGEROUS SUBSTANCES AND PROCESSES AND ITS PLACE IN EDUCATION - FESZTEROVA, Melania (Trends in education, 2012)
In practice we get acquaint with the changes which negatively affect the working environment and decrease of the safety in all industry branches (for example transportation, energy) and the increase of the lost time accidents. Occupational Health and Safety (OHS) is focused on decreasing an accident and injury rate, risk assessment and precaution using progressive arrangements from practice, education and support of consciousness that leads to the complex improvement of the welfare, increasing of "culture of work" and school preparation. The paper highlights the importance of discipline "Dangerous substances and processes" in the education process for future graduates of bachelor study program OHS.
Keywords: education; Dangerous substances and processes; Occupational Health and Safety (OHS).